Optimalisasi Edukasi Kewirausahaan Sejak Dini Sebagai Daya Ungkit Inovasi MI Al-Mustawa Gunung Sindur Kabupaten Bogor - Widayani Wahyuningtyas; Aniek Irawatie; Suprima Suprima; Hermina Hermina; Hairunnisa Br. Sagala; Abdullah Arif (PELITA NUSA TENGGARA, 2026)
This Community Service (PKM) program aims to optimize the instillation of entrepreneurial values ​​from an early age at Al Mustawa Elementary School (MI) in Gunung Sindur, Bogor Regency, as a lever for innovation at the school. This program was implemented to address the limited understanding of entrepreneurship, which was previously defined solely as